Role of National Green Tribunal in Forest Conservation: An Analysis - Kumar, Mihir (Indian Forester, 2022)
The World has been facing with the challenges of Environmental Protection. Every year, we are witnessing complex issues arising out of many forms of environmental hazards. The year 2021 is no exception. In a populous country like India, certain unique issues arise as majority of the Indians follow the principle of ’anthropocentrism’ and the regulators sometimes favour corporate centrism. On the legal side, there appears to be no major or new policy decision taken by the Union and State governments for environmental protection. In recent years, there has been a sustained focus on the role played by the higher judiciary in devising and monitoring the implementation of measures for pollution control, conservation of forests and climate change. The Stockholm conference, 1972 worked as a catalyst in development of environmental jurisprudence in India. Legislative and executive efforts have been made in the field of environmental law. The Forest (Conservation) Act, 1980, Air (Prevention and Control of Pollution) Act, 1981, Environmental (Protection) Act, 1986, Protection of Plant Variety and Farmers Right Act, 2001, Biological Diversity Act, 2002, Wild Life (Protection) Amendment Act, 2002 and National Green Tribunal Act, 2010 (NGT) were enacted. The aim and objective was to protect and improve the natural environment including forest and climate change and to have compassion for living creatures.